2019
DOI: 10.29219/fnr.v63.3437
|View full text |Cite
|
Sign up to set email alerts
|

Cod protein powder lowered serum nonesterified fatty acids and increased total bile acid concentrations in healthy, lean, physically active adults: a randomized double-blind study

Abstract: BackgroundFish fillet consumption is associated with beneficial health effects; however, little is known about whether consuming other parts of the fish such as head, backbone, skin, cut-offs, and entrails (collectively known as residuals) will provide comparable effects.ObjectiveThe aim of the study was to investigate if daily supplementation with cod residual protein powder would impact lipid metabolism in healthy adults.MethodsForty healthy, lean, physically active participants (18 women, 22 men) with norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…However, these changes did not differ from the placebo group, hence the results should be interpreted with caution. In line with findings from previous intervention studies with low doses of cod protein in healthy, overweight adults [ 20 ] and normal-weight adults [ 33 ], we observed reduced levels of LDL-C within the CPH group. However, a reduction in LDL-C was also observed within the placebo group, and no differences were found when comparing the two groups.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, these changes did not differ from the placebo group, hence the results should be interpreted with caution. In line with findings from previous intervention studies with low doses of cod protein in healthy, overweight adults [ 20 ] and normal-weight adults [ 33 ], we observed reduced levels of LDL-C within the CPH group. However, a reduction in LDL-C was also observed within the placebo group, and no differences were found when comparing the two groups.…”
Section: Discussionsupporting
confidence: 91%
“…Secondly, the participants in the current trial only received a daily morning dose of CPH. Previous studies have suggested that distributing the doses throughout the day might lead to a more potent effect due to a constant flow of bioactive peptides in circulation [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…All capsules for the study were produced at Pharmatech AS (Fredrikstad, Norway). A detailed description of the production of intervention capsules is described elsewhere [21] and the contents of the capsules are presented in Table 1. Trimethylamine N-oxide (TMAO) content in the cod residual powder and placebo capsules was determined using the micro-diffusion assay described by Conway and Byrne [32] and anserine was measured by High Performance Liquid Chromatographyusing the Waters Pico-Tag method [33].…”
Section: Production and Analyses Of Intervention Capsulesmentioning
confidence: 99%
“…Power analysis was not feasible for the original study, which was designed as a pilot study and is the first to investigate effects of cod residuals on circulating markers of lipid metabolism in lean adults [21]. Therefore, no estimation of sample size for the current measurements was conducted prior to the study.…”
Section: Sample Sizementioning
confidence: 99%
See 1 more Smart Citation